Price setting before and during the pandemic: Evidence from Swiss consumer prices - Barbara Rudolf; Pascal Seiler (ETH Zurich, KOF Swiss Economic Institute, 2022)
We provide new evidence on price rigidity at the product level based on microdata underlying the Swiss consumer price index from 2008 to 2020. We find that the frequency o f price changes has increased over the last decade, particularly among products where collection switched to online prices, reflecting t he r ise o f e -commerce. Furthermore, p rice changes tend to be synchronized within rather than across stores. Time variations in inflation can be attributed mainly to variations in the frequency of both price increases and price decreases. In the first year of the pandemic, the frequency of price adjustments changed little on average, while temporary sales responded countercyclically to the respective demand conditions across sectors.
hdl:20.500.11850/581467
Keywords: E31; E5; L11; 330; Price rigidity; price-setting behavior; consumer prices; inflation; COVID-19 pandemic